Biomass piezoelectric loss composite sound absorption material and preparation method and application thereof

By loading biomass adhesive on the melamine foam matrix and embedding piezoelectric material to form a multi-level composite structure, the problems of low low-frequency absorption efficiency and poor stability of existing sound-absorbing materials are solved, and low-cost and high-efficiency low-frequency sound wave absorption is achieved, which is suitable for aerospace, automotive and other fields.

CN120636353APending Publication Date: 2025-09-12CHONGQING UNIV OF TRADITIONAL CHINESE MEDICINE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511009008.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-22
Publication Date
2025-09-12

AI Technical Summary

Technical Problem

Existing sound-absorbing materials have low absorption efficiency for low-frequency sound waves (≤500 Hz), high cost, complex process, high density, and piezoelectric composite materials are prone to falling off and uneven dispersion, resulting in poor stability and poor sound absorption performance.

Method used

A melamine foam matrix is ​​used to load the biomass adhesive, and piezoelectric material is embedded in the adhesive to form a multi-level composite structure. The sound absorption performance is enhanced by the viscoelasticity and piezoelectric effect of the biomass adhesive, and the preparation process is simplified by combining the freeze-drying process.

Benefits of technology

It significantly improves the absorption efficiency of low-frequency sound waves (100~500 Hz), reduces production costs, simplifies the process, avoids the increase of material density, enhances the stability and sound absorption performance of the material, and is suitable for application scenarios with weight requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120636353A_ABST
    Figure CN120636353A_ABST
Patent Text Reader

Abstract

The invention relates to a biomass piezoelectric loss composite sound absorption material and a preparation method and application thereof. The biomass piezoelectric loss composite sound absorption material comprises a melamine foam base body, a biomass adhesive loaded on the melamine foam base body and a piezoelectric material embedded in the biomass adhesive. The invention also provides a preparation method of the biomass piezoelectric loss composite sound absorption material, which comprises the following steps: dispersing the piezoelectric material in a biomass adhesive solution to obtain mixed slurry; and immersing a melamine foam matrix into the mixed slurry, taking out the melamine foam matrix, and performing freeze drying to obtain the biomass piezoelectric loss composite sound absorption material. The invention further provides the biomass piezoelectric loss composite sound absorption material used for absorbing low-frequency sound waves. The problem that an existing sound absorption material is low in low-frequency sound wave (smaller than or equal to 500 Hz) absorption efficiency is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of acoustic functional materials, and in particular to a biomass piezoelectric loss composite sound-absorbing material, a preparation method thereof, and applications thereof. Background Art

[0002] In the field of sound-absorbing materials, traditional materials such as polyester fiber and polyurethane foam are widely used. These materials primarily absorb sound wave energy through pore resonance and viscous loss mechanisms. However, traditional sound-absorbing materials focus on absorbing mid- and high-frequency sound waves and have significant shortcomings in absorbing low-frequency sound waves (frequency ≤ 500 Hz). Research has shown that the absorption efficiency of these materials for low-frequency sound waves is generally less than 40%. This is because low-frequency sound waves have relatively long wavelengths, and their energy is primarily concentrated near the surface of the material, making it difficult to penetrate deeply into the pore structure for effective resonance and viscous loss. Furthermore, the lower vibration frequency of low-frequency sound waves reduces the efficiency of the pore resonance mechanism, making it difficult to efficiently convert the sound wave energy into heat or other forms of energy for dissipation as effectively as absorbing mid- and high-frequency sound waves.

[0003] Several existing technologies are being used to improve the low-frequency performance of traditional sound-absorbing materials. For example, carbon nanotubes (CNTs) are added to materials to enhance their sound absorption. Carbon nanotubes, with their unique nanostructure and high surface area, can significantly improve the material's absorption efficiency for low-frequency sound waves. However, this approach has some significant drawbacks. First, the high production cost of CNTs significantly increases the cost of CNT-added sound-absorbing materials, limiting their feasibility for large-scale applications. Second, uniformly dispersing CNTs in traditional sound-absorbing materials is a complex process. CNTs tend to agglomerate, making it difficult to achieve an ideal dispersion within the material matrix. This not only affects the material's sound absorption performance but can also lead to a decrease in its mechanical properties. Furthermore, the addition of CNTs often increases the material's density, making it unsuitable for applications with strict weight requirements (such as aerospace and automotive interiors), thus limiting its application.

[0004] Another approach to improving the low-frequency performance of traditional sound-absorbing materials is to design resonant cavity structures. Resonant cavity structures can absorb specific low-frequency sound waves by adjusting the size and shape of the cavity. However, the manufacturing process for such structures is complex, requiring precise machining and assembly, which increases production costs and time. Furthermore, resonant cavity structures are typically fragile and susceptible to damage from external environmental influences (such as vibration and impact) during actual use, resulting in reduced sound absorption performance. Furthermore, resonant cavity structures are relatively large and occupy a considerable amount of space, making them difficult to meet practical requirements in space-constrained applications (such as small electronic devices and compact building spaces).

[0005] Piezoelectric materials, such as barium titanate, offer a new approach to addressing low-frequency sound absorption. Piezoelectric materials exhibit a unique piezoelectric effect, which converts the mechanical energy of sound waves into electrical energy, thereby dissipating the sound wave energy. When sound waves act on piezoelectric materials, the electrical polarization within the material changes, causing charge separation and forming an electric field. Through appropriate circuit design, this electrical energy can be effectively dissipated, achieving the desired sound absorption. This piezoelectric-based sound absorption mechanism differs from the pore resonance and viscous loss mechanisms of traditional sound-absorbing materials. It is not limited by the long wavelength of low-frequency sound waves and, in theory, can achieve high sound absorption efficiency in the low-frequency range.

[0006] However, the application of piezoelectric materials in the field of sound absorption also faces many technical difficulties. Piezoelectric ceramics are one of the common piezoelectric materials, but there are great difficulties in combining them with porous matrix materials. Piezoelectric ceramics usually have high hardness and brittleness, and are difficult to effectively bond with soft porous matrix materials (such as polyester fibers, polyurethane foam, etc.). In practical applications, piezoelectric ceramics easily fall off the surface of porous matrix materials, resulting in unstable sound absorption performance. In addition, the dispersion of piezoelectric ceramics in porous matrices is also a major challenge. Due to the strong electrostatic interaction between piezoelectric ceramic particles and the difference in interfacial energy with the matrix material, it is difficult to achieve uniform dispersion in the porous matrix. This uneven dispersion state not only affects the sound absorption performance of the piezoelectric material, but may also lead to local stress concentration, further exacerbating the problem of piezoelectric ceramic shedding. Summary of the Invention

[0007] In view of this, one of the objectives of the present invention is to provide a biomass piezoelectric lossy composite sound-absorbing material to solve the problem of low absorption efficiency of low-frequency sound waves (≤500 Hz) of existing sound-absorbing materials. A second objective of the present invention is to provide a preparation method and application of a biomass piezoelectric lossy composite sound-absorbing material to solve the problems of high cost, complex process and high density of existing sound-absorbing materials, as well as the problem of easy shedding and uneven dispersion of existing piezoelectric composite sound-absorbing materials, resulting in poor stability and affecting sound absorption performance.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A biomass piezoelectric loss composite sound-absorbing material comprises a melamine foam matrix, a biomass adhesive loaded on the melamine foam matrix, and a piezoelectric material embedded in the biomass adhesive.

[0009] According to the above technical approach, a melamine foam matrix with a porous structure that effectively scatters and damps sound waves is used, causing them to reflect and propagate multiple times within the foam, thereby increasing the propagation path and energy loss of the sound waves. A biomass adhesive is then loaded onto the matrix to form a continuous network structure. This network structure not only enhances the integrity and stability of the material but also increases the damping loss of sound waves during propagation. The viscoelastic properties of the biomass adhesive enable it to absorb and dissipate sound wave energy, further improving the material's sound absorption performance. Simultaneously, piezoelectric material particles are cleverly embedded within the biomass adhesive network. When sound waves act on the material, the piezoelectric particles generate electric charges. These charges form an electric field within the material, which further dissipates sound wave energy, thereby enhancing the material's sound absorption. The introduction of piezoelectric particles not only increases the material's damping loss but also improves its absorption capacity for low-frequency sound waves through an electroacoustic coupling mechanism. The melamine foam matrix, biomass adhesive and piezoelectric material form a multi-level composite structure of "foam-adhesive network-piezoelectric particles", which greatly improves the absorption efficiency of the composite sound-absorbing material for low-frequency sound waves and solves the problem of low absorption efficiency of existing sound-absorbing materials for low-frequency sound waves (≤500 Hz).

[0010] Preferably, the melamine foam matrix is ​​a fiber-type foam with a pore size between 50 and 300 μm.

[0011] Preferably, the biomass adhesive is selected from at least one of sodium carboxymethyl cellulose (CMC), chitosan, and sodium alginate.

[0012] Preferably, the piezoelectric material is selected from at least one of barium titanate (BTO), lead zirconate titanate (PZT) and potassium sodium niobate (KNN).

[0013] Preferably, the particle size of the piezoelectric material is between 0.1 and 5 μm.

[0014] Preferably, the biomass adhesive and the melamine foam matrix are both doped with a mixture of urea and phosphate.

[0015] Preferably, the phosphate is selected from at least one of ammonium dihydrogen phosphate, disodium hydrogen phosphate, sodium tripolyphosphate and sodium hexametaphosphate.

[0016] Preferably, the phosphate is selected from ammonium dihydrogen phosphate.

[0017] The present invention also provides a method for preparing a biomass piezoelectric loss composite sound-absorbing material, comprising the following steps: S1. dispersing the piezoelectric material in the biomass adhesive solution to obtain a mixed slurry; S2. Immersing the melamine foam matrix in the mixed slurry, taking it out and freeze-drying it to obtain a biomass piezoelectric loss composite sound-absorbing material.

[0018] The method for preparing a biomass piezoelectric lossy composite sound-absorbing material of the present invention achieves efficient preparation of the material by dispersing the piezoelectric material in a biomass adhesive solution to form a mixed slurry, then immersing the melamine foam matrix in the mixed slurry and freeze-drying it. Among them, biomass adhesives are usually derived from renewable resources and are relatively low in cost. In addition, biomass adhesives have the advantages of being green, degradable, and having good film-forming properties. They can stably load piezoelectric particles on the foam skeleton, and their active groups (such as -COO⁻) can also enhance interfacial bonding. In addition, compared with traditional high-temperature curing or complex chemical treatment processes, the freeze-drying process is simple to operate and has low energy consumption, thereby reducing overall production costs. This preparation method mixes the piezoelectric material with the biomass adhesive and then directly impregnates it on the melamine foam matrix. The mixture is formed in one step by freeze-drying, avoiding complex multi-step synthesis and processing processes, simplifying the production process, and improving production efficiency. Melamine foam itself has a porous structure with a high expansion ratio and large porosity. Combined with the use of a biomass adhesive to disperse piezoelectric nanomaterial particles during the synthesis process, this effectively avoids pore blockage caused by ion aggregation and adhesive thermal shrinkage, thereby significantly reducing the overall density of the material. During the preparation process, the biomass adhesive and piezoelectric material are evenly dispersed within the pores of the foam without significantly increasing the overall density of the material. This low density makes the material more suitable for applications requiring minimal weight, such as aerospace and automotive, while maintaining good sound absorption performance. The introduction of the piezoelectric material enhances the material's absorption capacity for low-frequency sound waves, while the viscoelastic properties of the biomass adhesive further improve the absorption efficiency of mid- and high-frequency sound waves. This multi-stage composite structure not only solves the problem of low absorption efficiency of existing sound-absorbing materials at low frequencies, but also improves the material's overall performance.

[0019] The biomass piezoelectric loss composite sound-absorbing material prepared by the preparation method of the present invention solves the problems of low efficiency and limited performance improvement of traditional sound-absorbing materials in low-frequency sound absorption by cleverly combining piezoelectric materials with a porous matrix, as well as the shortcomings of high cost, complex process and excessive density caused by adding carbon nanotubes or designing a resonant cavity structure.

[0020] Preferably, the biomass adhesive solution is a biomass adhesive aqueous solution with a mass percentage of biomass adhesive of 0.5-15%.

[0021] Preferably, the mass percentage of the piezoelectric material in the mixed slurry is 2-6%.

[0022] Preferably, the melamine foam substrate is immersed in the mixed slurry for 1 to 8 hours.

[0023] Preferably, the freeze-drying temperature is -55 to -45°C, and the time is 12 to 24 hours.

[0024] By freeze-drying at -55~-45 ℃, the cross-linked mesh structure of the adhesive can be well preserved while removing moisture, avoiding covering and blocking of the pores on the matrix surface due to thermal shrinkage of the adhesive.

[0025] Preferably, the preparation method further includes: S3, immersing the freeze-dried biomass piezoelectric loss composite sound-absorbing material in a mixed aqueous solution of urea and phosphate, so that the biomass adhesive and the melamine foam matrix are doped with urea and phosphate, taking out and vacuum drying to obtain a biomass piezoelectric loss composite sound-absorbing material with enhanced performance.

[0026] By immersing the freeze-dried biomass piezoelectric lossy composite sound-absorbing material in a mixed solution of urea and phosphate, urea and phosphate form a hydrophobic-cross-linked network inside the material, which significantly enhances the moisture resistance of the biomass piezoelectric lossy composite sound-absorbing material. In addition, the urea and phosphate are evenly distributed inside the biomass piezoelectric lossy composite sound-absorbing material by the impregnation method, ensuring that the performance improvement is throughout the whole material without local defects, thereby ensuring the overall performance of the biomass piezoelectric lossy composite sound-absorbing material.

[0027] Preferably, the molar ratio of urea to phosphate is 1:1.

[0028] Preferably, the total mass fraction of urea and phosphate in the mixed aqueous solution is 15-25%.

[0029] Preferably, the immersion time is 1 to 5 hours.

[0030] The present invention also provides an application of a biomass piezoelectric loss composite sound-absorbing material, wherein the biomass piezoelectric loss composite sound-absorbing material is used for absorbing low-frequency sound waves of 100 to 500 Hz.

[0031] Preferably, the biomass piezoelectric loss composite sound-absorbing material is used as a low-frequency sound insulation material in a wall interlayer and / or ceiling structure.

[0032] Preferably, the biomass piezoelectric loss composite sound-absorbing material is used as a noise reduction material in the motor compartment of a new energy vehicle and / or the floor of a high-speed rail carriage.

[0033] Preferably, the biomass piezoelectric loss composite sound-absorbing material is used as a wrapped noise reduction material in compressor and / or fan ducts.

[0034] Beneficial effects of the present invention: The biomass piezoelectric loss composite sound-absorbing material of the present invention forms a multi-level composite structure of "foam-adhesive network-piezoelectric particles" by loading a biomass adhesive on melamine foam and embedding a piezoelectric material in the biomass adhesive. The synergistic effect of piezoelectric conversion and porous structure is then utilized to greatly improve the absorption efficiency of the composite sound-absorbing material for low-frequency sound waves.

[0035] The preparation method of the biomass piezoelectric loss composite sound-absorbing material of the present invention comprises the following steps: dissolving a biomass adhesive in a solvent to form a viscous solution; adding piezoelectric powder to disperse into a slurry; and impregnating foam with the slurry before freeze-drying and solidifying. The synergistic effect of piezoelectric dissipation and the porous structure significantly improves the absorption efficiency of low-frequency sound waves (100-500 Hz) (the sound absorption coefficient at 150 Hz reaches 0.65), thereby solving the problem of insufficient low-frequency performance of traditional sound-absorbing materials. The method has promotional and application value in the field of acoustic functional material technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 is the SEM image; Figure 2 is the XRD pattern; Figure 3 is the FTIR spectrum; Figure 4 It is the frequency curve of sound absorption coefficient. DETAILED DESCRIPTION

[0037] The following will describe the embodiments of the present invention with reference to preferred embodiments. Those skilled in the art will readily appreciate the other advantages and benefits of the present invention from the disclosure herein. The present invention may also be implemented or applied through various other specific embodiments, and the details in this specification may be modified or altered based on different viewpoints and applications without departing from the spirit of the present invention. It should be understood that the preferred embodiments are intended only to illustrate the present invention and are not intended to limit the scope of protection of the present invention.

[0038] Example 1 A method for preparing a biomass piezoelectric loss composite sound-absorbing material comprises the following steps: S1. Prepare 200 mL of a CMC aqueous solution with a CMC content of 5% by mass, add BTO powder with a particle size of 1 μm to the CMC aqueous solution, and ultrasonically disperse for 30 minutes to form a uniform slurry to obtain a mixed slurry. The mass percentage of BTO in the mixed slurry is 4%; S2, the size of 100 × 100 × 20 mm 3 The melamine foam matrix was immersed in the mixed slurry prepared in S1 for 6 h, taken out and freeze-dried at a temperature of -50 °C for 12 h to solidify, thereby obtaining a biomass piezoelectric loss composite sound-absorbing material.

[0039] Example 2 A method for preparing a biomass piezoelectric loss composite sound-absorbing material comprises the following steps: S1. Prepare 200 mL of a CMC aqueous solution containing 5% chitosan by weight, add BTO powder with a particle size of 1 μm to the CMC aqueous solution, and ultrasonically disperse for 30 minutes to form a uniform slurry to obtain a mixed slurry. The mass percentage of BTO in the mixed slurry is 4%; S2, the size of 100 × 100 × 20 mm 3 The melamine foam matrix was immersed in the mixed slurry prepared in S1 for 6 h, taken out and freeze-dried at a temperature of -50 °C for 12 h to solidify, thereby obtaining a biomass piezoelectric loss composite sound-absorbing material.

[0040] Example 3 A method for preparing a biomass piezoelectric loss composite sound-absorbing material comprises the following steps: S1. Prepare 200 mL of a CMC aqueous solution with a CMC content of 5% by mass, add PZT powder with a particle size of 1 μm to the CMC aqueous solution, and ultrasonically disperse for 30 minutes to form a uniform slurry to obtain a mixed slurry. The mass percentage of PZT in the mixed slurry is 4%; S2, the size of 100 × 100 × 20 mm 3 The melamine foam matrix was immersed in the mixed slurry prepared in S1 for 6 h, taken out and freeze-dried at -50 °C for 12 h to obtain a biomass piezoelectric loss composite sound-absorbing material.

[0041] Example 4 A method for preparing a biomass piezoelectric loss composite sound-absorbing material comprises the following steps: S1. Prepare 200 mL of a CMC aqueous solution having a CMC content of 5% by mass, add KNN powder having a particle size of 1 μm to the CMC aqueous solution, and ultrasonically disperse for 30 minutes to form a uniform slurry to obtain a mixed slurry. The mass percentage of KNN in the mixed slurry is 4%; S2, the size of 100 × 100 × 20 mm 3 The melamine foam matrix was immersed in the mixed slurry prepared in S1 for 6 h, taken out and freeze-dried at a temperature of -50 °C for 12 h to solidify, thereby obtaining a biomass piezoelectric loss composite sound-absorbing material.

[0042] Example 5 A method for preparing a biomass piezoelectric loss composite sound-absorbing material comprises the following steps: S1. Prepare 200 mL of a CMC aqueous solution with a CMC content of 5% by mass, add BTO powder with a particle size of 1 μm to the CMC aqueous solution, and ultrasonically disperse for 30 minutes to form a uniform slurry to obtain a mixed slurry. The mass percentage of BTO in the mixed slurry is 4%; S2, the size of 100 × 100 × 20 mm 3 The melamine foam matrix is ​​immersed in the mixed slurry prepared in S1 for 6 hours, taken out and freeze-dried at -50 °C for 12 hours to solidify, thereby obtaining a biomass piezoelectric loss composite sound-absorbing material; S3. Immerse the biomass piezoelectric lossy composite sound-absorbing material obtained in S2 in a 20% urea / ammonium dihydrogen phosphate mixed solution (molar ratio 1:1) for 3 hours, take it out and vacuum dry it to obtain a biomass piezoelectric lossy composite sound-absorbing material with enhanced moisture resistance.

[0043] Example 6 A method for preparing a biomass piezoelectric loss composite sound-absorbing material comprises the following steps: S1. Prepare 200 mL of a CMC aqueous solution containing 5% chitosan by weight, add BTO powder with a particle size of 1 μm to the CMC aqueous solution, and ultrasonically disperse for 30 minutes to form a uniform slurry to obtain a mixed slurry. The mass percentage of BTO in the mixed slurry is 4%; S2, the size of 100 × 100 × 20 mm 3 The melamine foam matrix is ​​immersed in the mixed slurry prepared in S1 for 6 hours, taken out and freeze-dried at -50 °C for 12 hours to solidify, thereby obtaining a biomass piezoelectric loss composite sound-absorbing material; S3. Immerse the biomass piezoelectric lossy composite sound-absorbing material obtained in S2 in a 20% urea / ammonium dihydrogen phosphate mixed solution (molar ratio 1:1) for 3 hours, remove it, and vacuum dry it to obtain a biomass piezoelectric lossy composite sound-absorbing material with enhanced moisture resistance.

[0044] Example 7 A method for preparing a biomass piezoelectric loss composite sound-absorbing material comprises the following steps: S1. Prepare 200 mL of a CMC aqueous solution with a CMC content of 5% by mass, add PZT powder with a particle size of 1 μm to the CMC aqueous solution, and ultrasonically disperse for 30 minutes to form a uniform slurry to obtain a mixed slurry. The mass percentage of PZT in the mixed slurry is 4%; S2, the size of 100 × 100 × 20 mm 3The melamine foam matrix is ​​immersed in the mixed slurry prepared in S1 for 6 hours, taken out and freeze-dried at -50 °C for 12 hours to solidify, thereby obtaining a biomass piezoelectric loss composite sound-absorbing material; S3. Immerse the biomass piezoelectric lossy composite sound-absorbing material obtained in S2 in a 20% urea / ammonium dihydrogen phosphate mixed solution (molar ratio 1:1) for 3 hours, take it out and vacuum dry it to obtain a biomass piezoelectric lossy composite sound-absorbing material with enhanced moisture resistance.

[0045] Example 8 A method for preparing a biomass piezoelectric loss composite sound-absorbing material comprises the following steps: S1. Prepare 200 mL of a CMC aqueous solution having a CMC content of 5% by mass, add KNN powder having a particle size of 1 μm to the CMC aqueous solution, and ultrasonically disperse for 30 minutes to form a uniform slurry to obtain a mixed slurry. The mass percentage of KNN in the mixed slurry is 4%; S2, the size of 100 × 100 × 20 mm 3 The melamine foam matrix is ​​immersed in the mixed slurry prepared in S1 for 6 hours, taken out and freeze-dried at -50 °C for 12 hours to solidify, thereby obtaining a biomass piezoelectric loss composite sound-absorbing material; S3. Immerse the biomass piezoelectric lossy composite sound-absorbing material obtained in S2 in a 20% urea / ammonium dihydrogen phosphate mixed solution (molar ratio 1:1) for 3 hours, take it out and vacuum dry it to obtain a biomass piezoelectric lossy composite sound-absorbing material with enhanced moisture resistance.

[0046] Comparative Example 1 The size without any treatment is 100×100×20 mm 3 The melamine foam substrate is used as control example 1.

[0047] Comparative Example 2 A method for preparing CMC composite foam comprises the following steps: S1. Prepare 200 mL of CMC aqueous solution with a CMC mass percentage of 5%; S2, the size of 100 × 100 × 20 mm 3 The melamine foam matrix was immersed in the CMC aqueous solution in S1 for 6 h, taken out and freeze-dried at -50 °C for 12 h to obtain a CMC composite foam.

[0048] Detection and Analysis 1) Scanning electron microscopy (SEM) analysis The biomass piezoelectric loss composite sound-absorbing material with enhanced moisture resistance prepared in Example 5, the melamine foam matrix in Control Example 1, and the CMC composite foam prepared in Control Example 2 were subjected to SEM tests, respectively. The results are as follows: Figure 1 shown.

[0049] Figure 1 The medium foam + CMC + BTO corresponds to the biomass piezoelectric loss composite sound-absorbing material with enhanced moisture resistance prepared in Example 5, the foam corresponds to the melamine foam matrix in Control Example 1, and the foam + CMC corresponds to the CMC composite foam in Control Example 2.

[0050] from Figure 1 Analysis shows that the melamine foam matrix in Control Example 1 has smooth pore walls. The CMC composite foam in Control Example 2 has a continuous film layer on its surface. The moisture-resistant biomass piezoelectric lossy composite sound-absorbing material prepared in Example 5 inherits the porous properties of melamine foam, and the loading process does not cause significant pore blockage or other changes. Furthermore, the pore walls of the moisture-resistant biomass piezoelectric lossy composite sound-absorbing material prepared in Example 5 are covered with dense nano-protrusions (BTO particles embedded in the CMC network), significantly increasing the specific surface area by approximately three times compared to pure foam.

[0051] 2) XRD analysis The biomass piezoelectric loss composite sound-absorbing material with enhanced moisture resistance prepared in Example 5 and the melamine foam matrix in Control Example 1 were subjected to XRD tests, respectively. The results are as follows: Figure 2 shown.

[0052] Figure 2 The medium foam + CMC + BTO corresponds to the biomass piezoelectric loss composite sound-absorbing material with enhanced moisture resistance prepared in Example 5, the foam corresponds to the melamine foam matrix in Control Example 1, and the foam + CMC corresponds to the CMC composite foam in Control Example 2.

[0053] from Figure 2 The analysis shows that the melamine foam matrix in Control Example 1 has no characteristic crystalline phase peak. The CMC composite foam in Control Example 2 is only amorphous. The biomass piezoelectric loss composite sound-absorbing material with enhanced moisture resistance prepared in Example 5 has a BTO characteristic peak (31.5° <110> , 45.2° <200> ), specifically, BTO characteristic diffraction peaks (JCPDS 05-0626) appeared at 2θ=31.5° and 45.2°, and the crystallinity of the piezoelectric phase was >95%.

[0054] 3) FTIR analysis The biomass piezoelectric loss composite sound-absorbing material with enhanced moisture resistance prepared in Example 5, the melamine foam matrix in Control Example 1, and the CMC composite foam prepared in Control Example 2 were subjected to FTIR tests, respectively. The results are as follows: Figure 3 shown.

[0055] Figure 3 In the embodiment, foam + CMC + BTO corresponds to the biomass piezoelectric loss composite sound-absorbing material with enhanced moisture resistance prepared in Example 5, foam corresponds to the melamine foam matrix in Control Example 1, and foam + CMC corresponds to the CMC composite foam prepared in Control Example 2.

[0056] from Figure 3 The comparative analysis shows that the biomass piezoelectric loss composite sound-absorbing material with enhanced moisture resistance prepared in Example 5 has a high -1 The peak width at (OH / NH vibration) is weakened, indicating that CMC destroys the original hydrogen bond network of the foam. -1 A new -COO⁻ asymmetric stretching vibration peak (CMC characteristic) was added at 814cm, which proved that CMC was successfully modified on the foam surface; -1 The BTO lattice vibration peak appears at , indicating that the piezoelectric phase is successfully loaded.

[0057] 4) Sound absorption performance test According to GB / T 18696.2 standard, the moisture-resistant biomass piezoelectric loss composite sound-absorbing material prepared in Example 5, the melamine foam matrix in Control Example 1, and the CMC composite foam prepared in Control Example 2 were tested for sound absorption performance. The results are as follows: Figure 4 and as shown in Table 1.

[0058] Table 1 Sound absorption performance results from Figure 4 As can be seen from the analysis in Table 1, the moisture-resistant biomass piezoelectric loss composite sound-absorbing material prepared in Example 5 has a sound absorption coefficient at 300 Hz that is 67.3% higher than that of the pure foam (Control Example 1), thereby demonstrating that the biomass piezoelectric loss composite sound-absorbing material of the present invention greatly improves the absorption efficiency of low-frequency sound waves (≤500 Hz) through the synergistic effect of the piezoelectric dissipation of the piezoelectric nanomaterial, the biomass adhesive, and the porous structure of the melamine foam matrix.

[0059] 5) Moisture resistance test In order to evaluate the moisture resistance of sound-absorbing foam, a wet heat environment exposure test was carried out on the biomass piezoelectric loss composite sound-absorbing material.

[0060] The specific procedure is as follows: First, the test samples (one each from the CMC / BTO group, which had been soaked and one from the unsoaked group) were removed, weighed, and their initial thickness measured. Subsequently, the samples were placed in a constant temperature and humidity chamber (set at 40±2°C, 85±5% RH) for 24 hours. After exposure, the samples were quickly removed, and any visible surface moisture was gently blotted with absorbent paper. The wet mass was then immediately measured. The samples were then allowed to recover in a standard indoor environment for 24 hours before being weighed again. The material's stability and performance retention under high humidity conditions were comprehensively evaluated by calculating the rate of mass change between the wet state and after recovery, and by observing changes in appearance (such as deformation and mildew) and the recovery of key properties (sound absorption coefficient). The results are shown in Table 2.

[0061] Table 2 Humidity resistance test results As can be seen from Table 2, the mass change rate of the biomass piezoelectric lossy composite sound-absorbing material with enhanced moisture resistance prepared in Example 5, after further soaking in urea / diammonium phosphate, is significantly lower than that of the untreated biomass piezoelectric lossy composite sound-absorbing material prepared in Example 1. A comparison of the changes in the 300 Hz sound absorption coefficient before and after the humidity resistance test of Examples 1 and 5 reveals that, while the sound absorption performance of both materials decreases under the influence of a humid environment, the decrease in sound absorption performance of the biomass piezoelectric lossy composite sound-absorbing material with enhanced moisture resistance prepared in Example 5, after soaking in urea / diammonium phosphate, under the influence of a humid environment is significantly less.

[0062] 6) Cyclic stability test The specific operation is as follows: the biomass piezoelectric loss composite sound-absorbing material with enhanced moisture resistance prepared in Example 5 is weighed, and then subjected to 10 cycles of compression (strain 50%), and then the compressed biomass piezoelectric loss composite sound-absorbing material with enhanced moisture resistance prepared in Example 5 is weighed again, the BTO particle shedding rate is calculated using the following formula, and the sound absorption coefficient at 300Hz after cyclic compression is measured. The results are as follows: Figure 4 shown.

[0063] Figure 4 , after compression, corresponds to the sound absorption coefficient of the biomass piezoelectric loss composite sound-absorbing material with enhanced moisture resistance prepared in Example 5 after cyclic compression.

[0064] The BTO particle shedding rate = [(the mass of the biomass piezoelectric loss composite sound-absorbing material before compression - the mass of the biomass piezoelectric loss composite sound-absorbing material after compression) / the mass of the biomass piezoelectric loss composite sound-absorbing material before compression] × 100%.

[0065] The measured calculations show that the BTO particle shedding rate of the biomass piezoelectric loss composite sound-absorbing material with enhanced moisture resistance prepared in Example 5 is less than 4.7%; and Figure 4 From the comparative analysis, it can be seen that the moisture-resistant biomass piezoelectric loss composite sound-absorbing material prepared in Example 5 has a sound absorption coefficient attenuation of <8% at 300 Hz.

[0066] In summary, the biomass piezoelectric loss composite sound-absorbing material of the present invention has a sound absorption coefficient of 0.65 at 150 Hz (300% higher than that of pure foam), BTO particles are firmly attached through the CMC network, and the shedding rate is less than 5% after 10 cycles of compression. XRD shows characteristic lattice peaks of BTO (2θ=31.5°, 45.2°), confirming the successful loading of the piezoelectric phase ( Figure 2 ).

[0067] The above embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Any equivalent substitution or modification made by those skilled in the art based on the present invention is within the protection scope of the present invention.

Claims

1. A biomass piezoelectric loss composite sound-absorbing material, characterized in that: The invention comprises a melamine foam matrix, a biomass adhesive loaded on the melamine foam matrix, and a piezoelectric material embedded in the biomass adhesive.

2. The biomass piezoelectric loss composite sound-absorbing material according to claim 1, characterized in that: The melamine foam matrix is ​​a fiber-type foam with a pore size between 50 and 300 μm; And / or, the biomass adhesive is selected from at least one of sodium carboxymethyl cellulose (CMC), chitosan, and sodium alginate; and / or, the piezoelectric material is selected from at least one of barium titanate (BTO), lead zirconate titanate (PZT), and potassium sodium niobate (KNN); And / or, the particle size of the piezoelectric material is between 0.1 and 5 μm.

3. The biomass piezoelectric loss composite sound-absorbing material according to claim 1, characterized in that: The biomass adhesive and the melamine foam matrix are both doped with a mixture of urea and phosphate.

4. The biomass piezoelectric loss composite sound-absorbing material according to claim 3, characterized in that: The phosphate is selected from at least one of ammonium dihydrogen phosphate, disodium hydrogen phosphate, sodium tripolyphosphate and sodium hexametaphosphate.

5. A method for preparing the biomass piezoelectric loss composite sound-absorbing material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. dispersing the piezoelectric material in the biomass adhesive solution to obtain a mixed slurry; S2. Immersing the melamine foam matrix in the mixed slurry, taking it out and freeze-drying it to obtain a biomass piezoelectric loss composite sound-absorbing material.

6. The preparation method according to claim 5, characterized in that The biomass adhesive solution is a biomass adhesive aqueous solution with a mass percentage of 0.5-15% of the biomass adhesive; And / or, the mass percentage of the piezoelectric material in the mixed slurry is 2-6%.

7. The preparation method according to claim 5, characterized in that The melamine foam substrate is immersed in the mixed slurry for 1 to 8 hours; And / or, the freeze-drying temperature is -55 to -45°C, and the time is 12 to 24 hours.

8. The preparation method according to claim 5, characterized in that Also includes: The freeze-dried biomass piezoelectric loss composite sound-absorbing material is immersed in a mixed aqueous solution of urea and phosphate, taken out and vacuum-dried to obtain a biomass piezoelectric loss composite sound-absorbing material with enhanced performance.

9. The preparation method according to claim 8, characterized in that The molar ratio of urea to phosphate is 1:1; The total mass fraction of urea and phosphate in the mixed aqueous solution is 15-25%; And / or, the immersion time is 1 to 5 hours.

10. An application of the biomass piezoelectric loss composite sound-absorbing material according to any one of claims 1 to 4, characterized in that: The biomass piezoelectric loss composite sound-absorbing material is used to absorb low-frequency sound waves of 100 to 500 Hz; And / or, the biomass piezoelectric loss composite sound absorbing material is used as a low-frequency sound insulation material in a wall interlayer and / or ceiling structure; And / or, the biomass piezoelectric loss composite sound-absorbing material is used as a noise reduction material in the motor compartment of a new energy vehicle and / or the floor of a high-speed rail carriage; And / or, the biomass piezoelectric loss composite sound-absorbing material is used as a wrapped noise reduction material in compressor and / or fan ducts.